Analysis of Current and Electrode Types on Welding Defects in ASTM A36 Mild Steel - Herisiswanto Herisiswanto; Yohanes Yohanes; Khoirul Hafisuddin (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2022)
The purpose of this study is to analyze the welding defects that occurring in the SMAW (Shielded Metal Arc Welding) process. This study used experimental method to investigate the various types of electrodes and welding current. The welding process in this study used ASTM A36 low carbon steel with specimen dimensions of 8 mm thick, 80 mm wide, and 100 mm long. The welding process was carried out in an underhand position (1G) using a V-seam layer with a SMAW welding machine, which a sliding adaptive two axis system with speed control. The types of electrodes used were E6013 and E7018 electrodes with a diameter of 3.2 mm. The current variations used 90 A, 105 A and 120 A. The test methods used the Penetrant Test, Visual Test (Non Destructive Test) and Tensile Test (Destructive Test). The results of this study were: 1) the welding defects that often occurring at the E6013 electrode due to undercut and at the E7018 electrode caused by the porosity, 2) at a current of 120 A the occurrence of welding defects was minimal, and 3) the tensile strength of E7018 was greater than E6013.